(untitled) (REMUNOM, 2025)
The article addresses the rehabilitation of the historic building that housed the first bank in Formoso do Araguaia, TO. This building, located in the city center, played a crucial role in local economic development and has architectural features representative of its time. However, prolonged abandonment resulted in significant degradation, impacting the cultural and urban heritage of the region. The project proposes preserving the original features of the building, combining historical restoration with adaptations that meet contemporary demands. Based on detailed surveys, the work used software such as Revit and Twinmotion for three-dimensional modeling and realistic visualization of the planned interventions. The proposals include restoring the facade, restructuring the roof, restoring window frames, and redesigning the interior spaces for multifunctional functions, such as cultural and commercial areas. In addition to enhancing the historic heritage, the project seeks to promote positive cultural and social impact, revitalizing the urban environment and strengthening community pride. The approach balances respect for original construction techniques with modern and sustainable solutions, highlighting the importance of rehabilitating historic buildings as an essential part of collective memory and local development.